Searching for Refuge: Challenges in the Contemporary Muslim World - Shafiq, Muhammad (Cross currents, 2017)
The article discusses the challenges of Muslim countries relating to their political and identity issues. It mentions the information on Qur'anic verses about hijrah and the Muslim history with focus on medieval terminologies of dar al harb (abode of warfare). It also mentions the Qur'an stands for worship, protection of human rights, and human dignity.